The Relationship Between Waist–Hip Ratio and Physical Activity Among Medical Students - Nurul Maulia Mustafa; Indah Lestari Daeng Kanang; Ilma Khaerina Amaliyah Bakhtiar; Imran Safei; Sigit Dwi Pramono (Ann Publisher, 2026)
Background: Physical inactivity contributes to central obesity and metabolic disorders among young adults with sedentary academic lifestyles. Waist–Hip Ratio (WHR) is a sensitive indicator of abdominal fat distribution and cardiometabolic risk, and medical students are particularly vulnerable due to demanding study schedules. Aim: To analyze the relationship between physical activity level and WHR among medical students of the Faculty of Medicine, Universitas Muslim Indonesia, Class of 2022. Methods: A cross-sectional study included 80 students selected through simple random sampling. Physical activity was measured using the Global Physical Activity Questionnaire (GPAQ) and categorized as low, moderate, or high based on the MET-min/week metric. WHR was assessed using standardized anthropometry and classified according to the WHO Asian cut-offs. Data were analyzed using univariate statistics and the Chi-square test (p < 0.05). Results: Most respondents were female (75%) and aged 21 years (75%). Normal WHR was found in 62.5% of students, while 37.5% were classified as having central obesity. The majority engaged in moderate physical activity (61.3%), followed by low (20.0%) and high (18.8%) activity levels. A significant relationship was identified between physical activity level and WHR (p < 0.001). Students with low physical activity showed a higher proportion of central obesity (75.0%), whereas those with moderate and high activity were predominantly within normal WHR. Conclusion: Physical activity level is significantly associated with WHR among medical students. Promoting regular physical activity is essential to prevent central obesity and associated metabolic risks in this population.